2015
DOI: 10.1111/rurd.12040
|View full text |Cite
|
Sign up to set email alerts
|

Regional and Sectoral Foreign Direct Investment in Portugal Since Joining the European Union: A Dynamic Portrait

Abstract: Abstract:Despite the very few studies regarding FDI in Portuguese regions -especially regarding its effects -FDI can be an important catalyst for regional economic development and growth. This work studies the existing FDI in the Portuguese regions, analysing its distribution by NUTS III, the sectors in which FDI has more weight in each region, as well as it evolution between 1986 and 2009. Over the years analysed, the results show an increase in the number of firms with FDI in Portugal, although their relativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Paper by Romanian authors deals with tertiarization inside the industrial parks in the capital city, in close connection with deindustrialization and industrial delocalization (Cercleux, Peptenatu, Merciu, 2015). An example of research in Portugal is also cited, where it was confirmed that the increase and diversification of foreign direct investment coincided with the tertiarization of the economy, being closer to the productive specialization pattern of the country, while continuing to focus mainly on manufacturing (Melo, Ferreira-Lopes, Monteiro, 2015). Investigation of M. Lobanov (2014) is resulted in the determination of the possible structural changes and prospects of the territorial-production formations in CEE in the post-crisis period.…”
Section: Overview Of Previous Researchmentioning
confidence: 97%
“…Paper by Romanian authors deals with tertiarization inside the industrial parks in the capital city, in close connection with deindustrialization and industrial delocalization (Cercleux, Peptenatu, Merciu, 2015). An example of research in Portugal is also cited, where it was confirmed that the increase and diversification of foreign direct investment coincided with the tertiarization of the economy, being closer to the productive specialization pattern of the country, while continuing to focus mainly on manufacturing (Melo, Ferreira-Lopes, Monteiro, 2015). Investigation of M. Lobanov (2014) is resulted in the determination of the possible structural changes and prospects of the territorial-production formations in CEE in the post-crisis period.…”
Section: Overview Of Previous Researchmentioning
confidence: 97%
“…Firstly, foreign direct investment is approached as a component of the balance of payments (Matos 1973;Lopes 1996;Leite et al 2001). A second perspective seeks to understand the geographic location and microeconomic impact of foreign investment (Barbosa et al 2004;Barbosa 2009;Barbosa and Eiriz 2009;Cardoso 2011;Crespo et al 2009;Farinha and Mata 1996;Forte and Sarmento 2014;Gonçalves and Guimarães 1996;Guimarães et al 2000;Melo 2012;Melo et al 2015;Pantea 2011;Pinheiro and Sarmento 2013;Silva et al 2013;Simões 1993). Finally, other studies investigate the factors attracting FDI, in a much more policy-oriented perspective, in order to design the most effective public policies to attract foreign capital (Barroco et al 2014;Faria 2015;Júlio et al 2013;Leitão 2011;Severiano 2011;Simões 1988 and; Wenseleers and the public policies directing inward FDI; the evolution of inward and outward FDI flows, trying to characterize their main phases over more than one century; the identification of the main questions for debate and research coming out from this long-term perspective.…”
Section: Introductionmentioning
confidence: 99%